Independence Of SMK Class XI Students is Making Career Decision - Emilia Fitri; Khairani Khairani (Universitas Negeri Padang, 2019)
The students need to havebehavioral autonomyin deciding their career. However, There are some students who lack behavioral autonomyindeciding the career. This study was aimed at describing the studentsbehavioral autonomyin deciding their career in terms of (1) havingthe ability of decision making. (2) having power over the influence of others, and (3) having self-confidence. This research uses a quantitative method with a descriptive approach. The population of this research is Students of Class XI of SMKN 9 Padang amounted of 389 students andthe sampleis 197 students taken by using purposive sampling. The instrument used is a questionnaire. The data obtained are analyzed by using a percentage technique. The findings of this study are (1) The students' independence of class XI of SMKN 9 Padang in deciding their career in terms of having the ability to make decisions is in the independent category, (2) the students' independence of class XI of SMKN 9 Padang in making decision of career in terms of having the power to influence others is in the independent category, and (3) the student tsautonomy of Class XI of SMKN 9 Padang inmakingdecision of career in terms of having self-confidence is in the independent category. Thus, it can be concluded that commonly the students' independence of Class XI of SMKN 9 Padang in making decision of career is categorized independent.